Aluminium release by coated and uncoated fluid‐warming devices. (21st February 2019) - Perl, T.; Kunze‐Szikszay, N.; Bräuer, A.; Quintel, M.; Röhrig, A. L.; Kerpen, K.; Telgheder, U.
Summary: The use of fluid‐warming systems is recommended for infusion rates > 500 ml.h −1 to avoid peri‐operative hypothermia. Some fluid‐warming devices use disposable aluminium‐heated plates for heat transfer, but there is no protective coating to separate the fluid from the heated aluminium surface. It is unknown if this could promote release of aluminium into infusion fluids. We investigated a coated (Fluido compact) and an uncoated (enFlow) fluid‐warming device using normal saline or balanced electrolyte solution as infusion fluids, pumped through the heated disposables at flow rates of 2, 4 and 8 ml.min −1 for 60 min each. Aluminium concentrations in the fluid samples were analysed using graphite furnace atomic absorption spectrometry. With saline the coated and uncoated devices yielded aluminium concentrations below the level of quantification (< 128 μg.l −1 ). Similarly, balanced electrolyte solution in the coated device yielded aluminium concentrations < 128 μg.l −1 . However, balanced electrolyte solution in the uncoated device yielded aluminium concentrations of up to 6794 (3465–8002 [1868–7421]) μg.l −1 . Repeating this last study at a flow rate of 2 ml.min −1 resulted in quite high aluminium concentrations when the uncoated device was not heated (~1000 μg.l −1 ) and higher concentrations after the device was heated. We conclude that using uncoated aluminium plates in fluid‐warming systems can lead to a risk of administering potentially harmful concentrations of aluminium when balanced crystalloid solutions are used. The mechanism is unclear, but heat is in part involved. Coating for aluminium within medical devices in direct contact with infusion fluids should be recommended. Abstract : 수술 중 체온저하를 예방하기 위해 수액 주입속도가 500 ml.h ‐1 를 초과하는 경우 수액 가온기의 사용이 권장되고 있다. 일부 수액 가온기는 전열(heat transfer)을 위해 일회용 알루미늄 재질 가열판을 사용하나, 가열된 알루미늄 표면과 수액 을 분리하는 보호피막이 존재하지 않는다. 이로 인해 알루미 늄이 주입 수액으로 용출될 수 있는지의 여부는 알려지지 않 았다. 본 연구에서는 60분 동안 투여속도 2, 4, 8 ml.min ‐1 로 각각 가열판을 통과한 생리식염수 또는 균형 전해질 용액을 투여하여 코팅된 수액 가온기(Fluido compact)와 미코팅된 가온기(enFlow)를 조사하였다. 수액 표본의 알루미늄 농도는 원자 흡광 광도법(graphite furnace atomic absorption spectrometry)을 사용하여 분석하였다. 식염수의 경우, 코팅 및 미코팅된 가온기에서 검출된 알루미늄 농도가 정량 한계에미치지 못하는 것으로 나타났다(‹ 128 μg.l ‐1 ). 유사하게, 코팅 된 가온기의 균형 전해질 용액에서 검출된 알루미늄 농도는 128 μg.l 미만이었다. 그러나 미코팅된 가온기의 균형 전해질 용액에서 검출된 알루미늄 농도는 6794 (3465–8002 [1868–7421]) μg.l ‐1 에 달하는 것으로 나타났다. 해당 실험을 투여속도 2 ml.min ‐1 로 미코팅된 가온기로 가열을 하지 않은 상태에서 반복 수행한 결과, 상당히 높은 농도의 알루미늄이 검출되었 으며(~1000 μg.l ‐1 ) 가열된 이후의 농도는 더 높았다. 본 연구 는 균형 전해질 정질액을 사용하였을 때 수액 가온기 내 미코 팅 알루미늄 가열판이 잠재적으로 유해한 알루미늄 농도의 투 여 위험을 유발할 수 있다고 결론지었다. 해당 메커니즘은 불 분명하나 열과 부분적으로 관련이 있는 것으로 추정된다. 주 입 수액이 직접 접촉하는 의료기기 내 알루미늄의 코팅이 권 고되어야 한다.